PERAN GURU PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN PRESTASI NON AKADEMIK SISWA OLIMPIADE PAI: THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS TO IMPROVE NON ACADEMIC ACHIEVEMENT OF PAI OLYMPIC STUDENTS - Rishta Umu Habibah; Ainur Rofiq (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Abstract The objective of this research is to understand the role and the factors influencing the improvement of students' non-academic achievements at MA Permata Mojokerto. This study aims to gain an in-depth understanding of the role of Islamic Education teachers and the factors that influence the improvement of students' non-academic achievements in the Islamic Education Olympiad at MA Permata. This type of research is qualitative, using natural and unbiased field data collection methods. The informants in this study are the vice principal of curriculum, Islamic education subject teachers, Olympiad coaches, and students who participate in the Islamic Education Olympiad. The findings indicate that teachers play multiple roles: as educators and instructors, as mediators and facilitators, as mentors, and finally as motivators. The factors include student interest, specific expectations, environment, facilities and infrastructure, and coaches.